Cortical matrix remodeling as a hallmark of relapsing–remitting neuroinflammation in MR elastography and quantitative MRI - Silva, Rafaela Vieira; Morr, Anna S.; Herthum, Helge; Koch, Stefan Paul; Mueller, Susanne; Batzdorf, Clara Sophie; Bertalan, Gergely; Meyer, Tom; Tzschaetzsch, Heiko; Kuehl, Anja A.; Boehm-Sturm, Philipp; Braun, Juergen; et al. (Acta Neuropathologica, 2024)
Multiple sclerosis (MS) is a chronic neuroinflammatory disease that involves both white and gray matter. Although gray matter damage is a major contributor to disability in MS patients, conventional clinical magnetic resonance imaging (MRI) fails to accurately detect gray matter pathology and establish a clear correlation with clinical symptoms. Using magnetic resonance elastography (MRE), we previously reported global brain softening in MS and experimental autoimmune encephalomyelitis (EAE). However, it needs to be established if changes of the spatiotemporal patterns of brain tissue mechanics constitute a marker of neuroinflammation. Here, we use advanced multifrequency MRE with tomoelastography postprocessing to investigate longitudinal and regional inflammation-induced tissue changes in EAE and in a small group of MS patients. Surprisingly, we found reversible softening in synchrony with the EAE disease course predominantly in the cortex of the mouse brain. This cortical softening was associated neither with a shift of tissue water compartments as quantified by T2-mapping and diffusion-weighted MRI, nor with leukocyte infiltration as seen by histopathology. Instead, cortical softening correlated with transient structural remodeling of perineuronal nets (PNNs), which involved abnormal chondroitin sulfate expression and microgliosis. These mechanisms also appear to be critical in humans with MS, where tomoelastography for the first time demonstrated marked cortical softening. Taken together, our study shows that neuroinflammation (i) critically affects the integrity of PNNs in cortical brain tissue, in a reversible process that correlates with disease disability in EAE, (ii) reduces the mechanical integrity of brain tissue rather than leading to water accumulation, and (iii) shows similar spatial patterns in humans and mice. These results raise the prospect of leveraging MRE and quantitative MRI for MS staging and monitoring treatment in affected patients.<br
Keywords: Magnetic resonance elastography; Tomoelastography; Multiple sclerosis; Experimental autoimmune encephalomyelitis; Cerebral cortex; Perineuronal nets